2021
DOI: 10.1021/acsaelm.1c00342
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Study on the Kinetic Formation of the Orthorhombic Ferroelectric Phase in Epitaxial Y-Doped Ferroelectric HfO2 Thin Films

Abstract: The crystal structure and ferroelectric properties of 12- to 18 nm-thick epitaxial YO1.5-HfO2 films with 5–9% YO1.5 on (111)­ITO//(111)­YSZ substrates are investigated to clarify the formation mechanism of the ferroelectric phase. The ferroelectric orthorhombic phase can be obtained by transformation from the higher symmetric tetragonal phase by surmounting a relatively low energy barrier. The orthorhombic phase is obtained for 6% and 7% YO1.5-doped HfO2 films by heat treatment at 1000 °C. Although the 5% YO1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 54 publications
3
32
0
Order By: Relevance
“…Less (100) and (110) signal is observed for the 10:1 sample. While this might be explainable by increased tetragonal phase, this would not match to the electrical results, as other groups have reported that super-cooled tetragonal phase does not result in AFE-like behavior but reduced P R and P S [20,21]. Moreover, the shape of the {200} -peak is slightly changed for the 10:1 sample, as indicated by the smaller TiN-related shoulder and reduced intensity of the (200) shoulder at smaller angles.…”
Section: Invited Papermentioning
confidence: 63%
See 3 more Smart Citations
“…Less (100) and (110) signal is observed for the 10:1 sample. While this might be explainable by increased tetragonal phase, this would not match to the electrical results, as other groups have reported that super-cooled tetragonal phase does not result in AFE-like behavior but reduced P R and P S [20,21]. Moreover, the shape of the {200} -peak is slightly changed for the 10:1 sample, as indicated by the smaller TiN-related shoulder and reduced intensity of the (200) shoulder at smaller angles.…”
Section: Invited Papermentioning
confidence: 63%
“…unlikely as an origin for AFE-like behavior, since the operating temperature is far below the Curie temperature [31,32] and recent investigations demonstrated the irreversible nature of this phase transition [20,21]. Internal bias fields and domain wall pinning on the other side would require diffusion/drift processes during wake-up, which are not observed [22].…”
Section: Invited Papermentioning
confidence: 98%
See 2 more Smart Citations
“…As the Curie temperature is in the range of 350–550 °C, HfO 2 films are expected to consist mainly of that orthorhombic phase, which has been recently confirmed, demonstrating that the antiferroelectric-like behavior is driven by ferroelastic switching (90°-domain wall motion). However, for very high doping concentrations, the supercooled tetragonal phase may be preserved. , …”
Section: Introductionmentioning
confidence: 99%